ENERGETIC VALORIZATION OF SAWMILL RESIDUES THROUGH SLOW PYROLISIS PROCESS - Figueiró, Clarissa Gusmão; Carneiro, Angélica de Cássia Oliveira; Fialho, Lucas de Freitas; da Silva, Carlos Miguel Simões; Peres, Letícia Costa (Floresta, 2018)
Brazil is a large producer of sawmill wastes, commonly used to supply boilers and produce energy. In order to reduce unwanted characteristics of the material, thermochemical conversions through carbonization is an alternative. The aim of this study is to characterize the energetic proprieties of raw biomass and pyrolyzed biomass of sawmill residues. In order to analyze the environmental impact in the emission of pyrolysis gases, the behavior of gases during the thermic treatment was determined. Eucalyptus sp. and Pinus sp. residues slow pyrolysis was performed in an electric kiln, whose gases were conducted through a condensable gas recovery system and an online gas analyzer. The charcoal, bio-oil and non-condensable gases yields were estimated. The wood’s and charcoal’s proximate analysis (extractives, lignin, holocellulosis, ash content), higher heating value, equilibrium moisture and density were appraised. The wood’s chemical components were esteemed. Hardwood and softwood’s charcoal presented several differences, especially in yields due to types of lignin. Hardwoods produce a higher amount of acetic acid in slow pyrolysis. This acid was converted, mainly, in carbon dioxide and e a minor extent in methane and carbon monoxide. The gas release was affected by the temperature and wood’s composition. The main gases resulting from the slow pyrolysis of wood are CO2, CO, CH4, H2. The emission of this gases to the atmosphere in addition to increasing the environmental impact caused by the industry is still a waste of energy that could be harnessed more efficiently. Pyrolysis increased the energetic characteristics of sawmill waste. However, in spite of the advantages of carbonization, ways to mitigate the emission of gases emitted in an operational scale should be evaluated.